Fistula Between a Primary Sigmoid Large B-Cell Lymphoma and an Ovarian Teratoma. Issue 6 (22nd June 2022) - Accardo, Caterina; Ardu, Massimiliano; Di Candido, Francesca; Epifani, Gabriele; Cassini, Diletta; Bono, Francesca; Baldazzi, Gianandrea
ABSTRACT: Primary colorectal lymphoma is a rare neoplasm. We report the case of a fistula between a diffuse large B-cell lymphoma of the sigmoid colon and an ovarian teratoma. An emergent laparotomy for an acute abdomen in a 90-year-old woman was performed. A pelvic mass of 12 × 9 cm fistulized in the left colon was found with the presence of gas and free liquid within the abdomen. This is an extremely rare condition, and as far as we know, no cases of a fistula between a large B-cell colonic lymphoma and an ovarian teratoma are present in the literature.